Turbulence Characteristics of Cavitating Flows Downstream of Triangular Multiorifice Plates - Kai Zhang; Zhiyong Dong; Meixia Shi (Advances in Mathematical Physics)
Cavitating flow fields downstream of triangular multiorifice plates with different geometrical parameters were measured by PIV technique, and effects of orifice size, orifice number, and orifice layout on turbulence intensity and Reynolds stress were analyzed. The experimental results showed that the turbulence intensity and Reynolds stress downstream of the different multiorifice plates exhibited sawtooth-like profiles. Decrease in orifice size, increase in orifice number, and taking staggered layout could contribute to intensification of turbulence mixing and shear effects of multiple cavitating jets downstream of the multiorifice plates and thus reaching the expected cavitation effects.